High-dose vitamin D3 to improve outcomes in the convalescent phase of complicated severe acute malnutrition in Pakistan: a double-blind randomised controlled trial (ViDiSAM) - Javeria Saleem; Rubeena Zakar; Muhammad Salman Butt; Rameeza Kaleem; Asif Chaudhary; Jaya Chandna; David A. Jolliffe; Joseph Piper; Zaigham Abbas; Jonathan C. Y. Tang; William D. Fraser; Nick Freemantle; et al. (Nature Communications)
Abstract We have previously shown that high-dose vitamin D3 improved weight gain and neurodevelopmental indices in children receiving standard therapy for uncomplicated severe acute malnutrition (SAM). Here we present results of a randomised placebo-controlled trial in Lahore, Pakistan, to determine whether two oral doses of 200,000 international units (IU) vitamin D3 (the first administered on or before the day of hospital discharge and the second administered 14 days later) would benefit children aged 6-59 months during the convalescent phase of complicated SAM. Eligible participants were individually randomised to intervention vs. control arms with a one-to-one allocation ratio and stratification by hospital of recruitment using computer-generated random sequences. Double-blinding to treatment allocation was maintained by concealing allocation from participants’ parents or guardians, their medical care providers, and all trial staff. The primary outcome was mean weight-for-height or -length z-score (WHZ) at 2-month follow-up. Secondary efficacy outcomes included mean WHZ at 6-month follow-up and mean lean mass index, Malawi Development Assessment Tool (MDAT) scores and serum 25-hydroxyvitamin D (25[OH]D) concentrations at 2- and 6-month follow-up. The trial has now completed. 259 children were randomised (128 to vitamin D, 131 to placebo), of whom 251 (96.9%) contributed data to analysis of the primary outcome (123 allocated to vitamin D, 128 to placebo). At 2-month follow-up, participants allocated to vitamin D had significantly higher mean serum 25(OH)D concentrations than those allocated to placebo (adjusted mean difference [aMD] 100.0 nmol/L, 95% confidence interval [CI] 72.2–127.8 nmol/L). This was not associated with an inter-arm difference in mean WHZ at 2-month follow-up (aMD 0.02, 95% CI −0.20 to 0.23), or in any anthropometric or neurodevelopmental secondary outcome assessed at 2- or 6-month follow-up. The intervention was safe. In conclusion, high-dose vitamin D3 elevated mean serum 25(OH)D concentrations in children receiving standard therapy for complicated SAM in Pakistan, but did not influence any anthropometric or neurodevelopmental outcome studied. The trial was registered at ClinicalTrials.gov with the identifier NCT04270643.